Water Quality Characteristics of Jonge Telaga (Doline Pond) as Water Resources for the People of Semanu District Gunungkidul Regency - M. Widyastuti; Eko Haryono (Faculty of Geography, Universitas Gadjah Mada, 2016)
Abstract Doline ponds (telaga) have an important role as one of water resources in karst areas, especially during dry seasons in Gunungkidul. Recently, the doline ponds are facing various environmental problems, i.e. steadily decreasing water storage, water loss, and degrading water quality. The research aims to determine the characteristics of Jonge Telaga which include the continuity of flow, utilization, pollution sources, physical water quality (temperature, EC,TDS, TSS, and turbidity), chemical water quality (pH , NO2, NO3, NH4, PO4, BOD , COD, and detergent), and biological water quality (total coliform). In order to determine the characteristics of Jonge Telaga, the research was conducted using a survey method, i.e., observing the continuity of flow and measuring physical, chemical, and biological water quality. Initially, the water was sampled purposively based on the area and the depth of this doline pond. The qualitative description of the results shows that Jonge Telaga is a closed perennial doline pond, whose main pollution source comes from domestic activities, such as bathing and washing. According to the Governor Regulation of the Special Region of Yogyakarta Number 20 Year 2008 on Water Quality Standards, Jonge Telaga meets all of the water quality criteria, except the temperature and detergent, for a Class II water.Abstrak Telaga mempunyai peran penting sebagai salah satu sumberdaya air di daerah karst, khususnya pada musim kemarau di Kabupaten Gunungkidul. Pada saat ini telaga menghadapi berbagai permasalahan lingkungan yaitu simpanan air yang terus berkurang, air yang cepat hilang, dan penurunan kualitas air. Tujuan penelitian adalah untuk mengetahui karakteristik telaga yang meliputi kontiyuitas aliran, pemanfaatan, sumber pencemar, kualitas fisik air telaga (TDS, TSS, suhu, kekeruhan, DHL), kimia air (pH, NH4, PO4, NO2, NO3, BOD, COD, deterjen) dan biologi air (coliform total). Penelitian ini dilaksanakan berdasarkan metode survei. Untuk mengetahui karakteristik telaga dilakukan pengamatan kontinyuitas aliran, pengukuran kualitas air secara fisik, kimia dan biologi. Pengambilan sampel air dilakukan secara purposive mendasarkan pada luasan dan kedalaman telaga. Analisis hasil dilakukan secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa Telaga Jonge merupakan telaga yang tertutup dengan ketersediaan air menerus sepanjang tahun. Sumber pencemar utama telaga adalah kegiatan domestik (mandi dan cuci). Kualitas air Telaga Jonge menurut baku mutu air kelas II PERGUB DIY Nomor 20 Tahun 2008 masih di bawah ambang batas kecuali suhu dan deterjen.